2019
DOI: 10.1016/j.amepre.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Time to Follow-up After Colorectal Cancer Screening by Health Insurance Type

Abstract: Introduction:The purpose of this study was to test the hypothesis that patients with Medicaid insurance or Medicaid-like coverage would have longer times to follow-up and were less likely to complete colonoscopy compared with patients with commercial insurance within the same healthcare systems.Methods: A total of 35,009 patients aged 50-64 years with a positive fecal immunochemical test were evaluated in Northern and Southern California Kaiser Permanente systems and in a University of Texas safety-net system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
(52 reference statements)
0
7
0
Order By: Relevance
“… 4 - 6 However, in community-based studies, colonoscopy follow-up is much lower, with rates of 30% to 65% reported. 7 - 12 Patient barriers to completing colonoscopy after a positive FIT include costs of the procedure, comorbid conditions taking precedence or increasing procedural risk, social or logistic barriers such as transportation or finding someone to accompany them to the procedure, fear or anxiety, and belief that the test was a false positive (eg, hemorrhoids). 13 , 14 Provider and system failures have also been reported, including not contacting the patient and lack of referral.…”
Section: Introductionmentioning
confidence: 99%
“… 4 - 6 However, in community-based studies, colonoscopy follow-up is much lower, with rates of 30% to 65% reported. 7 - 12 Patient barriers to completing colonoscopy after a positive FIT include costs of the procedure, comorbid conditions taking precedence or increasing procedural risk, social or logistic barriers such as transportation or finding someone to accompany them to the procedure, fear or anxiety, and belief that the test was a false positive (eg, hemorrhoids). 13 , 14 Provider and system failures have also been reported, including not contacting the patient and lack of referral.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies examining the impact of health insurance type on follow‐up adherence in different medical fields vary, but many report that patients with private insurance were more likely to attend follow‐up appointments. For instance, Patel et al demonstrated that patients with private health insurance were more likely to attend postoperative appointments for tympanostomy tube insertion, while Breen et al showed that those with Medicaid were less likely to complete follow‐up colonoscopy after positive fecal occult blood tests 16,17 . Although those with private insurance are thought to have greater coverage and access to care, other factors could impact adherence to surveillance in our patient group.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding follow-up, among those with abnormal results (n = 125), only 19 (15.2%) had adequate follow-up. This low follow-up rate might relate to participants coming from medically underserved communities; research indicates ethnic minorities, uninsured/underinsured individuals, or those with lower education often experience inadequate follow-up [31][32][33]. However, these factors cannot fully explain the low follow-up rates among Asian men because, in the POP study, 46.7% of the non-Asian men with abnormal results had adequate follow-up despite being from medically underserved communities.…”
Section: Discussionmentioning
confidence: 85%